SAT-182 Bilateral Adrenal Hemorrhage with Clinically Preserved Adrenal Function Leading to the Diagnosis of Antiphospholipid Syndrome - Hurtado, Carolina (J Endocr Soc, 2020)
Background: Spontaneous bilateral adrenal hemorrhage (BAH) is a rare complication of antiphospholipid syndrome (APS), which is the most common identifiable risk factor for BAH. Although adrenal dysfunction is generally irreversible, adrenal function might be preserved or even recover in rare cases(1). Clinical case: A 48 year-old man with history of hypertension and gout presented with right upper quadrant abdominal pain following trauma to his left leg. He was found to have a left lower extremity deep vein thrombosis and bilateral pulmonary emboli (PE) and was started on anticoagulation therapy. He continued to have abdominal pain and a CT abdomen revealed BAH. Three am cortisol level was 21 mcg/dL (8–25 mcg/dL), ACTH 37 pg/mL (6–59 pg/mL), aldosterone <3 ng/dL (4–31 ng/dL), renin 2.6 ng/mL/hr (0.2–1.6 ng/mL/hr), sodium 130 mmol/L (135–146 mmol/L) and potassium 4.3 mmol/L (3.6–5.3 mmol/L). Patient was hemodynamically stable and did not report symptoms of adrenal insufficiency. Hypercoagulable work-up was consistent with APS and Lupus. Despite normal cortisol levels, he was started on hydrocortisone in the setting of anticoagulation and recent hemorrhage. Given low aldosterone with slightly high renin he was also started on fludrocortisone. Six weeks after discharge, his morning cortisol was 6 mcg/dL and ACTH was elevated at 76 pg/mL which was concerning for adrenal insufficiency. However, 250 mcg IM ACTH stimulation test showed peak cortisol of 17 mcg/dL which is considered adequate. Aldosterone and renin levels normalized so fludrocortisone was discontinued. Patient subsequently self-discontinued all medications for 1 month with no symptoms of adrenal insufficiency, and later restarted hydrocortisone on his own. Repeat ACTH stimulation test showed baseline ACTH 57 pg/mL with peak cortisol of 17 mcg/dL. Patient was tapered off hydrocortisone and displayed no subsequent symptoms of adrenal insufficiency. Conclusion: This case highlights the need to consider APS in patients with spontaneous BAH. Additionally, patients with BAH may have relatively preserved adrenal function. There is limited data to guide when steroid replacement is necessary for patients without clear adrenal insufficiency. It may be reasonable to monitor these patients off hydrocortisone replacement with close monitoring. 1. Ramon I, Mathian A, Bachelot A, et al. Primary adrenal insufficiency due to bilateral adrenal hemorrhage-adrenal infarction in the antiphospholipid syndrome: long-term outcome of 16 patients. J Clin Endocrinol Metab. 2013;98(8):3179–3189.